2013
DOI: 10.1055/s-0032-1330421
|View full text |Cite
|
Sign up to set email alerts
|

Non-Alcoholic Steatohepatitis Occurs in Celiac Disease and is Associated with Cellular Stress

Abstract: Stress-induced ligands and apoptosis are induced in CD. Prospective studies need to determine the exact role of cellular stress and apoptosis in the gut-liver axis and the clinical implications to screen for NAFLD in CD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 26 publications
0
7
0
3
Order By: Relevance
“…Some have speculated that cellular stress induced in CD patients may trigger the onset of NAFLD. [32] Intestinal permeability is increased in CD[33] as well as in NAFLD[17, 34], and SIBO, known to be increased both in CD[20] as well as in NAFLD[17, 18], may alter intestinal permeability. [35] Furthermore, increased intestinal permeability has been suggested as a potential trigger for the development of NASH in patients with hepatic steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some have speculated that cellular stress induced in CD patients may trigger the onset of NAFLD. [32] Intestinal permeability is increased in CD[33] as well as in NAFLD[17, 34], and SIBO, known to be increased both in CD[20] as well as in NAFLD[17, 18], may alter intestinal permeability. [35] Furthermore, increased intestinal permeability has been suggested as a potential trigger for the development of NASH in patients with hepatic steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…Serum Vit D is also reduced in patients with non-alcoholic fatty liver disease [25]. Surprisingly, there are multiple studies linking non-alcoholic fatty liver disease to CD [26,27,28]. Recently, it has been shown that Vit D acts as an immunomodulating agent and plays important roles in the pathogenesis of AIDs.…”
Section: Discussionmentioning
confidence: 99%
“…In overweight (body mass index, BMI = 25–29.9 kg/m 2 ) and obese (BMI ≥ 30 kg/m 2 ) patients weight reduction by 5%–10% results in a 20%–80% decrease in intrahepatic triglyceride content and serum aminotransferase activity [1,7,8,34,35]. The optimal weight loss goal seems to be 0.5–1.0 kg per week (although some authors suggest higher goals), with particular attention to visceral fat reduction [9,36,37]. In patients with NAFLD, reduction of 5% to 7% of the initial body weight is recommended, while in those with suspected or biopsy-proven NASH, the weight loss goal is higher (7% to 10%) [14].…”
Section: Lifestyle Interventionsmentioning
confidence: 99%
“…About 90% of NAFLD patients present at least one feature of the metabolic syndrome, while the fully symptomatic metabolic syndrome (diagnosed in 33% patients) is a significant risk factor for the progression from NAFL into NASH [4]. In addition, co-existence of other medical conditions, such as hypothyroidism, hypogonadism, obstructive sleep apnea, polycystic ovary syndrome, and celiac disease, may associate with or promote the progress of NAFLD into NASH [5,6,7,8,9]. Intestinal barrier damage and intestinal microbiota imbalance (lower concentration of Bacteroidetes and higher concentration of Firmicutes) may also promote the progression of the disease [10].…”
Section: Introductionmentioning
confidence: 99%